Examining Physical Workload and Manual Material Handling: A NIOSH Lifting Equation Analysis for Packing Workers at PT X - Roro Siti Karimah, Rahadian; Nourma Rhomadhoni, Muslikha; Ratriwardhani, Ratna Ayu; Sahri, Moch. (Universitas Nahdlatul Ulama Surabaya, 2023)
Data derived from the Nordic Body Map (NBM) questionnaire results at PT X in March 2023 revealed that approximately 55.5% of packing workers reported experiencing extreme pain in their back and waist, attributed to manual handling tasks. This study aims to evaluate the safety of manual handling activities associated with cardboard packaging for finished products. Employing a quantitative analytic research approach with an observational method, the study includes a population and sample of 9 packing workers at PT X. Physical workload is assessed using the Cardiovascular Load method, and an ergonomic risk evaluation is conducted using the Composite Lifting Index (CLI) calculation method, considering the multitasking nature of packing work. Findings from the physical workload measurements highlight that one worker has a %CVL above 30%, placing the workload of all packing workers in the